Dynamic Scheduling on Grid Environments - Bertogna, Mario Leandro (2010)
The work carried out in the thesis describes efficient virtual environments management. One of the main contributions is a middleware scheduling optimization based on Grid environments. Being the overall goal to get an optimal resource selection plus a coordinate task execution optimization. In particular, the research was related with the interaction between non trivial quality service and tasks distribution issues in meta-organizations. While linking allocation and policies belonging to virtual and local organizations.